Estimation of carbonaceous aerosol concentrations by means of a 3D-air mass residence time multiple linear regression model (3D-MLRM): A four-year study at a rural site in Germany - Konstantinos Dimitriou; Nikolaos Mihalopoulos; Laurent Poulain; Hartmut Herrmann (Atmospheric Environment, 2026)

Readiness of European laboratories for the revised EU Ambient Air Quality Directive: An interlaboratory comparison on levoglucosan, mannosan and galactosan in PM2.5 - Falk Mothes; Laurent Poulain; Jean-Luc Jaffrezo; Sophie Darfeuil; Rhabira Elazzouzi; Karl Espen Yttri; Hans Gundersen; Nicolas Bonnaire; Jean-Eudes Petit; Benjamin Bergmans; Eric Moïs; Theodoros Potouridis; et al. (Atmospheric Environment, 2026)

Retraction notice to “Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China” [Sci. Total Environ. 898 (2023) 165303] - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

The carbon dioxide radical anion as a reductant in water treatment and atmospheric chemistry: a review - Thomas Schaefer; Jonathan D. Raff; Mallikarjuna N. Nadagouda; Eric Lichtfouse; Dan Meyerstein; Hartmut Herrmann; Virender K. Sharma (Environmental Chemistry Letters, 2026)
The carbon dioxide radical anion, CO 2 ●− , is a highly reactive radical species involved in the reduction of the CO 2 greenhouse gas, organic synthesis, atmospheric aerosol chemistry, and treatment of halogenated compounds. In recent years, CO 2 ●− has emerged as a strong reductant, or single electron donor. Here we present techniques used to generate CO 2 ●− and we discuss applications to degrading pollutants such as halogenated alkanes. The potential occurrence of such reductions in water and aqueous aerosols is discussed, notably for the degradation of perfluoroalkyl substances. In the laboratory, CO 2 ●− is directly generated by either direct electrochemical reduction of CO 2 or hydrogen atom transfer of either formate salts with and without catalysts or ferrioxalate through photochemical or radiolytic processes. The CO 2 ●− has an ultraviolet spectrum, and CO 2 ●− vibration modes are characterized by fast kinetics using infrared and Raman spectroscopy. The second-order rate constants of the reactions of CO 2 ●− with halogenated alkanes, of -1.84 ± 0.22 V, are generally slower than that of the hydrated electron, of -2.87 V, and give a negative linear relationship with energy of lower unoccupied molecular orbital, suggesting single electron transfer mechanism in reducing the halogenated compounds.

Simulated atmospheric transformation of the tire additives in the aqueous phase: 6-PPD, 6-PPD quinone, diphenylguanidine, and dicyclohexylamine - Volkwin Kuntz; Natalie Kamprad; Bettina Seiwert; Thomas Schaefer; Hartmut Herrmann; Thorsten Reemtsma; Daniel Zahn (Environmental Pollution, 2026)

Tracing local and long-range aerosol emission areas using multi-method and multi-site analyses in central Europe - Shubhi Arora; Laurent Poulain; Radek Lhotka; Jaroslav Schwarz; Petr Vodička; Saliou Mbengue; Naděžda Zíková; Jakub Ondráček; Petra Pokorná; Vladimír Ždímal; Hartmut Herrmann (Atmospheric Environment, 2026)

Toluene photo-oxidation and secondary organic aerosol formation: EUROCHAMP-2020 multi-chamber experiments - Petro Uruci; Kalliopi Florou; Marco Paglione; Christos Kaltsonoudis; Bénédicte Picquet-Varrault; Jean-François Doussin; Mathieu Cazaunau; Ari Leskinen; Liqing Hao; Annele Virtanen; David M. Bell; Anke Mutzel; et al. (Journal of Atmospheric Chemistry, 2025)

Machine learning-enabled estimation and high-resolution forecasting of atmospheric VOCs - Bingqing Lu; Shuyue Zhang; Chao Liu; Gantuya Ganbat; Hartmut Herrmann; Xiang Li; Yang Zhao (Atmospheric Environment, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

Multi-element isotope fractionation analysis to investigate the photosensitized reactions of humic substance with 3-chloroaniline - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Herrmann Richnow (Water Research, 2025)

A twin site study of size-resolved composition, source apportionment and health impacts of aerosol particles in Morocco - Nabil Deabji; Khanneh Wadinga Fomba; Laurent Poulain; Chaoyang Xue; Abdelwahid Mellouki; Hartmut Herrmann (Atmospheric Environment, 2025)

Multi-element compound-specific stable isotope analysis (2H, 13C, 15N, 33/34S) to characterize the mechanism of sulfate and hydroxyl radical reaction and photolysis of benzothiazole - Haiyan Yu; Limin Ma; Steffen Kümmel; Xiao Liu; Thomas Schaefer; Hartmut Herrmann; Hans-Hermann Richnow (Water Research, 2025)

Carbon, hydrogen, nitrogen and chlorine isotope fractionation during 3-chloroaniline transformation in aqueous environments by direct photolysis, TiO2 photocatalysis and hydrolysis - Ning Min; Jun Yao; Hao Li; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2025)

Particle-bound mercury in Saharan dust-loaded particulate matter in Cabo Verde - Eduardo José dos Santos Souza; Khanneh Wadinga Fomba; Sofía Gómez Maqueo Anaya; Kerstin Schepanski; Sandra Maria Freire; Dušan Materić; Thorsten Reemtsma; Hartmut Herrmann (Journal of Hazardous Materials, 2025)

Trends of PM1 aerosol chemical composition, carbonaceous aerosol, and source over the last 10 years at Melpitz (Germany) - Samira Atabakhsh; Laurent Poulain; Alessandro Bigi; Martine Collaud Coen; Mira Pöhlker; Hartmut Herrmann (Atmospheric Environment, 2025)

Molecular characteristics of sea spray aerosols during aging with the participation of marine volatile organic compounds - Xueqi Ma; Kun Li; Shan Zhang; Narcisse Tsona Tchinda; Jianlong Li; Hartmut Herrmann; Lin Du (Science of The Total Environment, 2024)

High-level HONO exacerbates double high pollution of O3 and PM2.5 in China - Chao Liu; Bingqing Lu; Qian Wang; Zekun Zhang; Xue Meng; Juntao Huo; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2024)

Strong synergistic and antagonistic effects of quinones and metal ions in oxidative potential (OP) determination by ascorbic acid (AA) assays - Eduardo José dos Santos Souza; Khanneh Wadinga Fomba; Manuela van Pinxteren; Nabil Deabji; Hartmut Herrmann (Journal of Hazardous Materials, 2024)

The seasonal variation of Asian dust, anthropogenic PM, and their sources in Dushanbe, Tajikistan - Khanneh Wadinga Fomba; Oluwabamise Lekan Faboya; Nabil Deabji; Abduvosit Makhmudov; Julian Hofer; Eduardo J. dos Santos Souza; Konrad Müller; Dietrich Althausen; Safarali Sharipov; Sabur Abdullaev; Hartmut Herrmann (Atmospheric Environment, 2024)

The influence of long-range transported Saharan dust on the inflammatory potency of ambient PM2.5 and PM10 - Gerrit Bredeck; Eduardo J. dos S. Souza; Claudia Wigmann; Khanneh Wadinga Fomba; Hartmut Herrmann; Roel P.F. Schins (Environmental Research, 2024)

Influence of anthropogenic activities on metals, sugars and PAHs in PM10 in the city of Fez, Morocco: Implications on air quality - Nabil Deabji; Khanneh Wadinga Fomba; Eduardo José dos Santos Souza; Abdelwahid Mellouki; Hartmut Herrmann (Environmental Science and Pollution Research, 2024)
Particulate matter (PM) is an important component in the atmosphere, affecting air quality, health, radiation balance, and global climate. To assess regional air quality in the city of Fez, an intensive field campaign was carried out in the autumn of 2019 in the Middle Atlas region of Morocco. Aerosol sampling was performed simultaneously at two urban sites in the city of Fez: (1) Fez University (FU), a sub-urban site, and (2) Fez Parc (FP), an urban site located in the city center of Fez, using PM 10 collectors. Various laboratory analyses were carried out, including PM mass, trace metals, inorganic ions, OC/EC, sugar compounds, and PAHs. The results indicate that the PM 10 mass (61 ng m −3 ) was comparable at both sites, with a 37–107 ng m −3 range. Most of the 19 investigated PAHs at the FU site (10.2 ± 6.2 ng m −3 ) were low-molecular-weight PAHs, while the most abundant PAHs at the FP site (6.9 ± 3.8 ng m −3 ) were mainly higher-molecular-weight PAHs. A diagnostic ratio analysis at both sites indicated that PAHs originated from fossil fuel combustion and traffic emissions from diesel engines, with Ant/(Ant + Phe) and Flu/(Flu + Pyr) ratios averaging 0.22 and 0.84, respectively. PMF analysis identified traffic emissions as a major source (30%), with secondary inorganic aerosols (20%) and biomass burning (14%). Polar plots highlight the dominance of local anthropogenic activities in PM pollution, with vehicular emissions, industrial activities, and biomass burning. This study shows that local sources and combustion processes significantly contribute to PM 10 sources in Morocco, providing insights into air pollution mitigation in North Africa.

Positive matrix factorization of seasonally resolved organic aerosol at three different central European background sites based on nuclear magnetic resonance Aerosolomics data - Štěpán Horník; Petra Pokorná; Petr Vodička; Radek Lhotka; Jan Sýkora; Shubhi Arora; Laurent Poulain; Hartmut Herrmann; Jaroslav Schwarz; Vladimír Ždímal (Science of The Total Environment, 2024)

Carbon and hydrogen isotope fractionation of phthalates during photocatalysis reactions in aqueous solution containing Fe(III) complexes or iron minerals - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Oliver J. Lechtenfeld; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Water Research, 2023)

High-resolution mapping of regional VOCs using the enhanced space-time extreme gradient boosting machine (XGBoost) in Shanghai - Bingqing Lu; Xue Meng; Shanshan Dong; Zekun Zhang; Chao Liu; Jiakui Jiang; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2023)

RETRACTED: Reduced atmospheric sulfate enhances fine particulate nitrate formation in eastern China - Liang Wen; Likun Xue; Can Dong; Xinfeng Wang; Tianshu Chen; Ying Jiang; Rongrong Gu; Penggang Zheng; Hongyong Li; Ye Shan; Yujiao Zhu; Yong Zhao; et al. (Science of The Total Environment, 2023)

Carbon isotope fractionation of di-(2-ethylhexyl)-phthalate during photosensitized degradation by •OH and S O 4 · - for characterization of reaction mechanisms - Ning Min; Jun Yao; Hao Li; Junjie Zhu; Steffen Kümmel; Thomas Schaefer; Hartmut Herrmann; Hans Hermann Richnow (Chemical Engineering Journal, 2023)

Unraveling the O3-NOX-VOCs relationships induced by anomalous ozone in industrial regions during COVID-19 in Shanghai - Bingqing Lu; Zekun Zhang; Jiakui Jiang; Xue Meng; Chao Liu; Hartmut Herrmann; Jianmin Chen; Likun Xue; Xiang Li (Atmospheric Environment, 2023)

Corrigendum to “Chemical drivers of ozone change in extreme temperatures in eastern China” [Sci. Total Environ. 874 (2023) 162424] - Xue Meng; Jiakui Jiang; Tianshu Chen; Zekun Zhang; Bingqing Lu; Chao Liu; Likun Xue; Jianmin Chen; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2023)

Aqueous-phase photo-oxidation of selected green leaf volatiles initiated by OH radicals: Products and atmospheric implications - Kumar Sarang; Tobias Otto; Sahir Gagan; Krzysztof Rudzinski; Thomas Schaefer; Martin Brüggemann; Irena Grgić; Adam Kubas; Hartmut Herrmann; Rafal Szmigielski (Science of The Total Environment, 2023)

Chemical drivers of ozone change in extreme temperatures in eastern China - Xue Meng; Jiakui Jiang; Tianshu Chen; Zekun Zhang; Bingqing Lu; Chao Liu; Likun Xue; Jianmin Chen; Hartmut Herrmann; Xiang Li (Science of The Total Environment, 2023)

Sea Ice Microbiota in the Antarctic Peninsula Modulates Cloud-Relevant Sea Spray Aerosol Production - Manuel Dall’Osto; Dolors Vaqué; Ana Sotomayor-Garcia; Miguel Cabrera-Brufau; Marta Estrada; Teresa Buchaca; Montserrat Soler; Sdena Nunes; Sebastian Zeppenfeld; Manuela van Pinxteren; Hartmut Herrmann; Heike Wex; et al. (Frontiers in Marine Science, 2022)
Sea spray aerosol (SSA) formation plays a major role in the climate system. The Antarctic Peninsula (AP) is affected by the greatest warming occurring in the Southern Ocean; changes in cryospheric and biological processes are being observed. Whilst there is some evidence that organic material produced by ice algae and/or phytoplankton in the high Arctic contributes to SSA, less is known about Antarctic Sea ice (sympagic) regions. To gain insight into the influence of Antarctic Sea ice biology and biogeochemistry on atmospheric aerosol, we report simultaneous water-air measurements made by means of in situ aerosol chamber experiments. For the first time, we present a methodology showing that the controlled plunging jet aerosol chamber settings do not cause major cell disruption on the studied sea ice ecosystems. Larger sea ice phytoplankton cells (>20 µm; mainly diatoms) tend to sediment at the bottom of the chamber (during the 24h experiment) and likely have a minor role on SSA production. When comparing four chamber experiments - we find that the two producing more SSA are the ones with highest abundance of nanophytoplankton cells (<20 µm; mainly nanoflagellates) as well as viruses. Our marine biogeochemical data show two broad groups of dissolved organic carbon: one rich in carbohydrates and proteic material and one rich in humic-like substances; the latter enhancing SSA production. This work provides unique insights into sea ice productivity that modulates SSA production, with potentially significant climate impacts. Further studies of these types are advised in order to see how microbiology impacts the biogeochemical cycling of elements and how aerosols are formed and processed in cold regions.

A protocol for quantifying mono- and polysaccharides in seawater and related saline matrices by electro-dialysis (ED) – combined with HPAEC-PAD - Sebastian Zeppenfeld; Manuela van Pinxteren; Anja Engel; Hartmut Herrmann (Ocean Science, 2020)
An optimized method is presented to determine dissolved free (DFCHO) and dissolved combined carbohydrates (DCCHO) in saline matrices, such as oceanic seawater, Arctic ice core samples or brine using a combination of a desalination with electro-dialysis (ED) and high-performance anion exchange chromatography coupled to pulsed amperometric detection (HPAEC-PAD). Free neutral sugars, such as glucose and galactose, were found with 95 %–98 % recovery rates. Free amino sugars and free uronic acids were strongly depleted during ED at pH=8, but an adjustment of the pH could result in higher recoveries (58 %–59 % for amino sugars at pH=11; 45 %–49 % for uronic acids at pH=1.5). The applicability of this method for the analysis of DCCHO was evaluated with standard solutions and seawater samples compared with another established desalination method using membrane dialysis. DFCHO in field samples from different regions on Earth ranged between 11 and 118 nM and DCCHO between 260 and 1410 nM. This novel method has the potential to contribute to a better understanding of biogeochemical processes in the oceans and sea–air transfer processes of organic matter into the atmosphere in future studies.

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

Chemical characterization of sub-micrometer aerosol particles in the tropical Atlantic Ocean: marine and biomass burning influences - Manuela van Pinxteren; Björn Fiedler; Dominik van Pinxteren; Yoshiteru Iinuma; Arne Körtzinger; Hartmut Herrmann (Journal of Atmospheric Chemistry, 2015)

Mechanism development and modelling of tropospheric multiphase halogen chemistry: The CAPRAM Halogen Module 2.0 (HM2) - Peter Bräuer; Andreas Tilgner; Ralf Wolke; Hartmut Herrmann (Journal of Atmospheric Chemistry, 2013)

A GIS based approach to back trajectory analysis for the source apportionment of aerosol constituents and its first application - Dominik van Pinxteren; Erika Brüggemann; Thomas Gnauk; Konrad Müller; Christian Thiel; Hartmut Herrmann (Journal of Atmospheric Chemistry, 2010)

Towards an operational aqueous phase chemistry mechanism for regional chemistry-transport models: CAPRAM-RED and its application to the COSMO-MUSCAT model - Laurent Deguillaume; Andreas Tilgner; Roland Schrödner; Ralf Wolke; Nadine Chaumerliac; Hartmut Herrmann (Journal of Atmospheric Chemistry, 2009)

Uptake of the NO 3 Radical on Aqueous Surfaces - Matthias Schütze; Hartmut Herrmann (Journal of Atmospheric Chemistry, 2005)

Hochschulnachrichten - Christian Herrmann; Hartmut Asche (KN - Journal of Cartography and Geographic Information, 2003)

Main particulate matter components in Saxony (Germany) - Gerald Spindler; Konrad Müller; Hartmut Herrmann (Environmental Science and Pollution Research, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)